Adaptive evolution of microalgae Schizochytrium sp. under high salinity stress to alleviate oxidative damage and improve lipid biosynthesis. (November 2018) - Sun, Xiao-Man; Ren, Lu-Jing; Bi, Zhi-Qian; Ji, Xiao-Jun; Zhao, Quan-Yu; Huang, He
Highlights: Antioxidant enzymes were taken into account in a novel strain evaluation system. Adaptive evolution under high salinity improves cell growth and lipid production. Lipid productivity of evolved strain was increased by 1.96-fold. Evolved strain showed a significant drop in the ROS and MDA levels. The gene expression levels of SOD and CAT were upregulated in evolved strain. Abstract: Lipid accumulation of Schizochytrium sp. can be induced by stress condition, but this stress-induction usually reduce cell growth and cause oxidative damage, which can eventually lower the lipid yield. Here, adaptive laboratory evolution (ALE) combined high salinity was performed to enhance the antioxidant system and lipid accumulation. The final strain ALE150, which was obtained after 150 days, showed a maximal cell dry weight (CDW) of 134.5 g/L and lipid yield of 80.14 g/L, representing a 32.7 and 53.31% increase over the starting strain, respectively. Moreover, ALE150 exhibited an overall higher total antioxidant capacity (T-AOC) and lower reactive oxygen species (ROS) levels than the starting strain. Furthermore, the regulatory mechanisms responsible for the improved performance of ALE150 were analyzed by transcriptomic analysis. Genes related to the antioxidant enzymes and central carbon metabolism were up-regulation. Moreover, the metabolic fluxes towards the fatty acid synthase (FAS) and polyketide synthase (PKS) pathways were also changed.